(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
A mixed oxide of cobalt (Co-Mg-Al-O) was used as catalyst in the oxidation of two VOCs, toluene, 2-propanol and their mixture. In this work, the autocombustion method was employed to obtain the cobalt mixed oxide and their catalytic potential was evaluated in oxidation reactions. Co-Mg-Al-O oxide was prepared maintaining the ratio (Co2 + +Mg2 +/ Al3+) =1 and a fuel-oxidant ratio equal to 0.56. The chemical composition, structure and morphology of the cobalt mixed oxide were investigated by means of X-ray fluorescence (XRF), X-ray diffraction (XRD), textural analysis, temperature programmed reduction TPR) and scanning electron microscopy (SEM). Cobalt mixed oxide was active in the toluene and 2-propanol catalytic oxidation and their mixture. The results showed that the autocombustion synthesis is a promising method that obtains active catalysts for the removal of VOCs in short times of preparation.